The shariah ruling on the permissibility of seafood in hanafi and shafi'i jurisprudence: A comparative study in the light of the qur'an and hadith - Anzar Aquil; Noor Malihah; Eny Rahmawati; Husna Nashihin; Nurhuda Alfina Layalin; Ahmad Ahadi (Yayasan Azhar Amanaa Yogyakarta, 2025)
This paper presents a comparative analysis of the permissibility of seafood within the Hanafi and Shafi'i schools of Islamic jurisprudence. Although both schools derive their rulings from the Qur'an and Hadith, they offer divergent interpretations regarding various marine life. Whereas the Shafi'i madhab generally permits all types of seafood based on the broad textual evidence, the Hanafi school restricts permissible sea creatures chiefly to fish, relying on a more cautious and often literalist textual interpretation. By examining Qur'anic verses, Hadith evidence, the methodological underpinnings of classical jurisprudence, and the perspectives of various scholars, this study elucidates the historical and contextual basis for these legal differences. Furthermore, contemporary case studies are included to explore how these rulings affect dietary practices in Muslim communities today, thereby demonstrating the legal pluralism inherent in the Islamic juridical tradition.